Chemical Bath Deposition and Optical and Electrical Properties of Pure and Doped Fe2S3 Films - He, H.-Y.; Fei, J.; Lu, J. (Micro and Nanosystems, 2014)
Pure and doped Fe2S3 films with n- and p-type electrical conductions were successfully deposited using chemical bath deposition at room temperature by controlling S/Fe molar ratio in the bath solution and doping Cu+ and Sn4+ cation, respectively. The films were characterized by X-ray diffraction, scanning electron microscopy, ultraviolet-visible spectrophotometry, and electrical resistance measurement. The pure and Cu+-doped Fe2S3 films with the S/Fe3/2 were deposited. Meantime, the pure and Sn4+-doped Fe2S3 films with the S/Fe3/2 were also deposited. The films had the average transmittances of 20.1– 30.1 % in the wavelength range of 270–800 nm, the direct band gaps 1.85– 2.42 eV, and the indirect band gaps of 0.5–1.2 eV. The film with the S/Fe3/2 showed lower average transmittances, wider band gaps, and p-type conductivity, while the films with S/Fe3/2 showed higher average transmittances, narrower band gaps, and n-type conductivity. The Cu+ and Sn4+ dopings obviously increased the bandgap and transmittance of the films and decreased the resistances of the p-type and n-type films, respectively. The refractive index, extinction coefficient, optical conductivity, dielectric constant of the films were calculated with the transmittance and reflectance spectra. Excellent optical and electric properties indicate that the Fe2S3 films is new type of solar energy materials.
Keywords: optical property